Assessment of Tourism Suitability and Carrying Capacity of Selected Tourist Sites in Tinambac, Camarines Sur, The Philippines - Yumi Vivien V. De Luna (ASEAN Journal on Hospitality and Tourism, 2021)
Achieving sustainable tourism requires tourist site management that is based on empirical studies. This paper utilized the analyses of the tourism suitability index and Boullon’s Carrying Capacity Mathematical Model (BCCMM) in assessing four selected tourist sites of Tinambac, Camarines Sur, which offers a wide range of tourist destinations. Results showed that all four sites have the following suitability index and carrying capacity: 76.19% with 43 persons per day; 80.95% with 60 persons per day; 86.90% with 359 persons per day; and 91.67% with 612 persons per day, respectively. Based on the assessment, the four selected tourist sites are suitable for tourism destinations.